Acute and chronic arterial and venous effects of captopril in congestive cardiac failure. Issue 6705 (14th October 1989) - Capewell, S.; Taverner, D.; Hannan, W. J.; Muir, A. L.
Abstract : OBJECTIVE–To determine whether captopril alters peripheral venous tone in patients with congestive cardiac failure. DESIGN–Open study of patients at start of captopril treatment and three months later. SETTING–A hospital gamma camera laboratory. PATIENTS–16 Men with congestive cardiac failure in New York Heart Association class II or III, aged 57-73. INTERVENTIONS–Patients were initially given 500 micrograms sublingual glyceryl trinitrate followed by 25 mg oral captopril. The study was then repeated after three months' captopril treatment. MAIN OUTCOME MEASURES–Previously validated non-invasive radionuclide techniques were used to measure changes in central haemodynamic variables and peripheral venous volumes in the calf. RESULTS–After 25 mg captopril there were falls in blood pressure and relative systemic vascular resistance and increases in cardiac index and left ventricular ejection fraction. This was accompanied by a 16% increase in peripheral venous volume (95% confidence interval 13.4% to 18.4%, p less than 0.01), which compared with an 11% increase after 500 micrograms glyceryl trinitrate (10% to 12%, p less than 0.01). Eleven patients were restudied after three months' continuous treatment with captopril. The resting venous volume was higher than it had been initially, by about 10%, and increased by a further 8.4% after 25 mg captopril (5.4% to 11.4%, p less than 0.05). CONCLUSIONS–Captopril is an important venodilator. Venous and arterial dilatation are produced short term and during long term treatment.